Interaction of antifibrinolytic providing intrathecal in intraventricular blood: a systematic review and meta-analysis - Fitra; Rizki Meizikri; Rafif Alfayat; Imam Hidayat; Wahyu Asrizal, Cynthia (Journal of International Surgery and Clinical Medicine, 2023)
Introduction: Intraventricular hemorrhage refers to the presence of blood in the cerebroventricular system.  Intraventricular hemorrhage can lead to severe complications such as hydrocephalus. One of the therapeutic modalities for intraventricular hemorrhage is to perform CSF diversion using an external ventricular drain (EVD). To overcome complications related to the use of EVD, there have been several efforts to accelerate its excretion in ventricular blood, one of which is by intraventricular injection of fibrinolytic. The mixed results of studies on intraventricular fibrinolysis prompted investigators to conduct a review and meta-analysis of this treatment modality. Method: We conducted systematic reviews and meta-analyses on several literature databases and included articles in English. We were using the boolean operator AND to search for literature containing all keywords in the databases and analyze the data using SPSS and Revmann. Results: Unfavorable outcomes with the use of intraventricular fibrinolytic therapy in IVH occurred in a median of 51% of cases. The risk of an unfavorable outcome in IVH patients who received intraventricular fibrinolytic was 0.93 times compared to controls. The risk of an unfavorable outcome in IVH patients receiving rtPA and intraventricular urokinase was 0.95 and 0.73 times, respectively, compared to controls. The use of intraventricular fibrinolysis was able to reduce IVH volume by an average of 22.84 cc. The use of intraventricular fibrinolysis was able to improve the modified Graeb Score with an average change of 5.24 points Conclusion: Intraventricular fibrinolysis administration helps to reduce the risk of unfavorable outcomes in IVH cases.